A child, a passion, and a mission to fill the gap: Affective, social, and personal impacts of a German minority community archive - Wiśniewska-Drewniak, Magdalena; Kapała, Adriana; Rosa, Agnieszka; Siuda, Kamila (Archival science, 2026)
This article, based on empirical data, especially interviews conducted in August 2024, examines an independent community archive that currently operates in south-western Poland, in the region of Silesia. The German Minority Research Center’s main goal is to preserve German identity and language among Germans in Poland, to study and document the community history and popularize their input in the history of the region. The article focuses on social, affective, and personal impacts of the German Minority Research Center’s archive. Analysis indicates that the archive preserves endangered heritage, supports cultural initiatives, empowers women, and addresses minority issues like German identity. It builds trust within the minority community and helps create counter-narratives. Data also indicate the lack of trust of the German minority in Polish state (public) archives. Archival contributors experience both stress and satisfaction, gaining skills and career opportunities. However, sustainability and the emotional demands of archival work remain challenges. The article argues that independent archives like GMRC provide scholarly and community value, offering alternatives to mainstream institutions and fostering personal and collective reflection.